Assessment for education : standards, judgement and moderation - Klenowski, Valentina; Wyatt-Smith, Claire (Los Angeles, California : Sage, 2014)
The book will show you how practitioner use of achievement standards can improve learning, equity, social justice and accountability. Inside this book, you will learn about: - quality assessment and judgment practice - relationships across curriculum, assessment, teaching and learning - front-ending assessment based on the learner's needs - practitioner judgment approaches and standards - the conditions under which teacher assessment can be valid - principles derived from research of social moderation practices.
The transformation of assessment -- Why teachers need to understand standards -- A sociocultural perspective on teachers' judgement practice and learning -- Alignment and front-ending assessment -- Moderation and the use of standards -- How teachers can use standards to improve student learning -- Sustainable assessment cultures -- Assessment and digital literacies -- Futures-oriented assessment
Includes bibliographical references and index.
Keywords: EDUCATION EVALUATION